Evaluation of presepsin as a diagnostic tool in newborns with risk of early-onset neonatal sepsis - Pospisilova, Iva; Brodska, Helena L.; Bloomfield, Marketa; Borecka, Klara; Janota, Jan (Frontiers in Pediatrics, 2023)
Objectives: To evaluate the efficacy of presepsin (P-SEP) as a potential biomarker of early-onset neonatal sepsis (EOS) and compare it to other routinely used markers of inflammation. To establish the cut-off values of P-SEP for EOS. Study design: 184 newborns were prospectively recruited between January 2018 to December 2020. Newborns >34th gestational week with suspected infection were included up to 72 hours after delivery, and divided into three categories (i.e. unlikely, possible, and probable infection) based on risk factors, clinical symptoms and laboratory results. Values of plasma P-SEP were sequentially analyzed. Results: Median values of P-SEP in newborns with probable infection were significantly higher compared to healthy newborns (p=0.0000013) and unlikely infection group (p=0.0000025). The AUC for discriminating the probable infection group from the unlikely infection group was 0.845 (95% Cl: 0.708-0.921). The diagnostic efficacy of P-SEP was highest when used in combination with IL-6 and CRP (0.97; 95% CI: 0.911-0.990). The optimal cut-off value of P-SEP was determined to be 695 ng/L. Conclusion: P-SEP, when combined with IL-6 and CRP, may be utilized as a negative predictive marker of EOS (NPV 97.2 %, 95% CI: 93.3-101), especially in newborns at low to medium risk of infection.